Randomized study of interferon beta-1a, low-dose azathioprine, and low-dose corticosteroids in multiple sclerosis - Havrdova, E; Zivadinov, R; Krasensky, J; Dwyer, M G; Novakova, I; Dolezal, O; Ticha, V; Dusek, L; Houzvickova, E; Cox, J L; Bergsland, N; Hussein, S; et al. (Multiple sclerosis (Houndmills, Basingstoke, England), 2009)
BACKGROUND: Studies evaluating interferon beta (IFNbeta) for multiple sclerosis (MS) showed only partial efficacy. In many patients, IFNbeta does not halt relapses or disability progression. One strategy to potentially enhance efficacy is to combine IFNbeta with classical immunosuppressive agents, such as azathioprine (AZA) or corticosteroids, commonly used for other autoimmune disorders. OBJECTIVE: The Avonex-Steroids-Azathioprine study was placebo-controlled trial and evaluated efficacy of IFNbeta-1a alone and combined with low-dose AZA alone or low-dose AZA and low-dose corticosteroids as initial therapy. METHODS: A total of 181 patients with relapsing-remitting MS (RRMS) were randomized to receive IFNbeta-1a 30 microg intramuscularly (IM) once weekly, IFNbeta-1a 30 microg IM once weekly plus AZA 50 mg orally once daily, or IFNbeta-1a 30 microg IM once weekly plus AZA 50 mg orally once daily plus prednisone 10 mg orally every other day. The primary end point was annualized relapse rate (ARR) at 2 years. Patients were eligible for enrollment in a 3-year extension. RESULTS: At 2 years, adjusted ARR was 1.05 for IFNbeta-1a, 0.91 for IFNbeta-1a plus AZA, and 0.73 for combination. The cumulative probability of sustained disability progression was 16.8% for IFNbeta-1a, 20.7% for IFNbeta-1a plus AZA, and 17.5% for combination. There were no statistically significant differences among groups for either measure at 2 and 5 years. Percent T2 lesion volume change at 2 years was significantly lower for combination (+14.5%) versus IFNbeta-1a alone (+30.3%, P < 0.05). Groups had similar safety profiles. CONCLUSION: In IFNbeta-naïve patients with early active RRMS, combination treatment did not show superiority over IFNbeta-1a monotherapy.
Keywords: recidiva; Magnetic Resonance Imaging; Disability Evaluation; mozek; magnetická rezonanční tomografie; Humans; hormony kůry nadledvin; interferon beta; Atrophy; Disease Progression; posuzování pracovní neschopnosti; Double-Blind Method; Drug Administration Schedule; Interferon-beta; Interferon beta-1a; Prednisone; azathioprin; výsledek terapie; Administration, Oral; dvojitá slepá metoda; lidé; imunosupresiva; časové faktory; atrofie; Immunosuppressive Agents; prednison; imunologické faktory; Azathioprine; Multiple Sclerosis, Relapsing-Remitting; relabující-remitující roztroušená skleróza; Brain; Treatment Outcome; Immunologic Factors; Recurrence; Injections, Intramuscular; progrese nemoci; aplikace orální; Adrenal Cortex Hormones; prospektivní studie; injekce intramuskulární; kombinovaná farmakoterapie; Time Factors; rozvrh dávkování léků; Drug Therapy, Combination; interferon beta 1a; Prospective Studies